Ultrasound-Assisted Decalcification Process Optimizationof Carapace of Chinese Soft-shelled Turtle and Biochemical Characterization of Collagen - Qiongyu ZHAO; Jian HU; Caiyan LI; Shujie XU; Wei SONG (Shipin gongye ke-ji, 2022)
In order to determine the technological conditions for decalcification of the carapace from the Chinese soft-shelled turtle(Pelodiscus sinensis), the decalcification conditions were optimized under ultrasonic assisted treatment with hydrochloric acid as a decalcifying agent. The decalcification rate and collagen migration rate were employed as evaluation indicators to investigate the effects of six factors including hydrochloric acid concentration, material-to-liquid ratio, decalcified time, decalcified temperature, working time of ultrasonic gap and ultrasonic power. In basis of optimized single factors, the Box-Behnken design in the response surface was used to optimize the process conditions of turtle carapace decalcification and establish a mathematical model. The effects of ultrasound-assisted decalcification process on the structural properties of collagen were investigated through biochemical character such as Ultraviolet spectrum scanning, SDS-PAGE spectrum, Fourier infrared scanning, amino acid analysis and Circular dichroism spectrum. The results showed that the best process conditions for ultrasonic-assisted decalcification of the carapace were: 0.8 mol/L of hydrochloric acid concentration, 1:40 (g/mL) of material-to-liquid ratio, 60 min of decalcified time, 145 W of ultrasound and 30 s/30 s of ultrasonic gap. Under these conditions, the decalcification rate was 64.97%±1.03%, and the collagen migration rate was 3.22%±0.84%. The results showed that the subunit composition, triple helix structure and secondary structure of carapace collagen remained unchanged. Therefore, ultrasound-assisted hydrochloric acid exhibited a good effect on the decalcification of the carapace of the Chinese soft-shelled turtle, which would provide a basis for further study concerning extraction of collagen from the carapace of the Chinese soft-shelled turtle.